Influence of Regular Physical Activity on Warfarin Dose and Risk of Hemorrhagic Complications. Issue 6 (12th February 2014) - Shendre, Aditi; Beasley, Timothy Mark; Brown, Todd M.; Hill, Charles E.; Arnett, Donna K.; Limdi, Nita A.
<x xml:space="preserve">Abstract</x> Objective To determine the influence of regular physical activity on stable warfarin dose and risk of major hemorrhage in patients on chronic anticoagulation therapy. Design Regular physical activity (maintained over > 80% of visits) was ascertained by self‐report at initiation of warfarin therapy (target international normalized ratio [INR] = 2–3) in 1272 patients, with changes documented at monthly anticoagulation clinic visits in a population‐based prospective cohort. Multi‐variable linear regression and survival analysis, respectively, were used to assess influence on warfarin and risk of hemorrhage. Setting Outpatient anticoagulation clinic Participants 1272 anticoagulated patients Measurement and Main Results There were 683 (53.7%) patients who were regularly physically active (≥ 30 min ≥ 3 times/week). Physically active patients required warfarin doses that were 6.9% higher (p=0.006) than in physically inactive patients after controlling for sociodemographic factors, vitamin K intake, clinical factors, and genetic variations. The overall incidence of major hemorrhagic events was 7.6/100 person‐years (p‐yrs, 95% confidence interval [CI] 6.4–8.9) in our population. The incidence was lower for physically active patients (5.6/100 p‐yrs, 95% CI 4.2–7.2) than in inactive patients (10.3/100 p‐yrs, 95% CI 8.2–12.9, p=0.0004). Active patients had a 38% lower risk of hemorrhage (hazard ratio 0.62, 95% CI 0.42–0.98, p=0.03) compared with inactive patients. Conclusions Regular physical activity is associated with higher warfarin dose requirements and lower risk of hemorrhage. The influence of physical activity on drug response needs to be further explored, and the mechanisms through which it exerts these effects need to be elucidated.